Agricultural Information Sources for Farmers in Lesotho, Southern Africa - Richard W. Tenney; Thomas F. Trail (Journal of Applied Communications, 1985)
The baseline survey of the Lesotho Farming Systems Research (FSR) prototype areas was a collaborative effort of the Lesotho Ministry of Agriculture (MOA) Research Division and Washington State University's Farming Systems Research Project. The project's thrust was adaptive on-the farm demonstrations to stimulate farmers' interest and adoption.